FOOD NEOPHOBIA AND ACCEPTANCE OF TRADITIONAL FOODS AMONG CONSUMERS IN KENINGAU, SABAH, MALAYSIA - Ramli, Adilah Md; Sapinin, Nurul Asidahtul; Ibrahim, Shalawati (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
This study examined the level of neophobia among local consumers in Keningau, Sabah, and its association with sociodemographic factors. Food neophobia, an aversion to eating or avoiding unusual foods, can affect consumer behaviour and openness to food diversity. A total of 423 respondents from Keningau participated in the study. Data was collected using structured questionnaires and analysed through descriptive statistics and correlation tests. The findings showed that the overall level of food neophobia among local consumers was neutral (score: 33-46), with 56% (n=237) of respondents falling into the middle range of the food neophobia scale, while the lowest was neophobia (score: 47-67) with 5.7% (n=24). Sociodemographic analysis revealed moderate levels of food neophobia (neutral) in the following age categories of 18-24 years (n=82), Muslim (n=189), female (n=151), SPM (n=83), and from Kadazan/Dusun ethnicity (n=168). This group showed a moderate or neutral tendency to unusual traditional foods compared to other demographic categories. Correlation results (r2 = 0.197) have identified a weak but significant relationship between levels of food neophobia and the willingness to try traditional non-local food, indicating a relationship between levels of neophobia and willingness factor among consumers in the district. However, it is seen to be very weak. Overall, the study offers insights into consumer tendencies in the Keningau district, Sabah, regarding food neophobia. These findings can be served as basis for future research on aspects of food identity and the impact of accepting of traditional foods that do not originate from Sabah. Furthermore, it provides constructive guidance on food marketing strategies while assisting tourism policymakers in effectively incorporating local heritage food in Sabah.